Sustainable Economic Development in the Transition Countries, With a Retrospect of the Republic of Macedonia - Nikolovski, Aleksandar (Journal of Economic Development, Environment and People, 2013)
Sustainable development represents a civilization challenge that should meet the needs of today’s generations without jeopardizing the ability of the Earth to meet the needs of the future generations. This challenge, as an evolutionary process in which the social and economic development and the environment protection are independent, but mutual complementary components demands the solving of several issues The vision of sustainable economic development is based on the historical, cultural and political development of the countries. There is no unique way of sustainable development for different countries and therefore they cannot be made in the same way. The transition toward sustainable development represents a social choice that connects the global vision of the local needs and goals. The citizens must participate in the process of sustainable development. They must recognize the role they have in creating problems and finding solutions. In order to gain a general frame for the assessment of sustainable economic development it is necessary to integrate several methodologies and approaches toward the possible future generations for a quality and healthy life. One of the ways of assessing the results from the policies and the activities is the use of the principles and indicators according to which it is determined how much the countries work on sustainable development. Part of the indicators are generally accepted, and part are in a modeling phase. A systematic approach is necessary to see whether all indicators are necessary, and which of them are necessary for the assessment of sustainability. The economists do not have problems in executing the objective and quantitative indicators. The sociologists are facing many problems in the execution of indicators because of the immateriality of the life quality. However, the environment experts see problems when they are limited in the execution of indicators. Sustainable development is much more than a mutual connection between the economy, the law and the ecology in establishing relations between the indicators of sustainable development and the economic development are the basis for creating conceptual link between the different approaches toward sustainable economic development. The aim of this paper is the implementation of today’s relevant experiences, practices and theoretical knowledge expressed through the changes that are reflected in the life in the Republic of Macedonia: • Protection of natural resources • Sustainable production and consumption • Sustainable sources of energy and • Following and reporting about the conditions, supported by the following indica-tors: • Level of citizens’ involvement in the social activities • Number of companies that have an ecological strategy • Number of people involved in the planning process • Number local communities in the Republic of Macedonia, which are eco-logically oriented • Number of shops that sale home food and organically developed food • Number of companies for organic production • Renewable sources of energy in the Republic of Macedonia • The level of nitrogen dioxide in the atmosphere The elaboration of the final material will go through the following principles: Participation of local citizens. Key segment of the implementation of the Agenda 21; Short-term plans that support the municipalities that environmentally oriented; Local production, which is forced whenever possible; The oil, coal, gas, water should be saved and renewable sources of energ y should be used instead.